The Effectiveness of Facilities and Infrastructure Management in Supporting Digital-Based Learning at Public Elementary Schools in Ngawen District - Yosafat Dwi Widi Hutomo; Pardimin; Rejokirono (JURNAL MANAJEMEN PENDIDIKAN, 2026)
Digital transformation in education requires elementary schools to manage facilities and infrastructure effectively in order to support digital-based learning processes. This study aims to describe the management process of digital facilities and infrastructure, which includes planning, procurement, and maintenance, as well as the effectiveness of such management in supporting the success of digital-based learning at Public Elementary Schools in Ngawen District, Klaten Regency. This study employed a quantitative approach using a survey method. Data were collected through the distribution of questionnaires to 78 respondents consisting of principals, teachers, and administrative staff from several Public Elementary Schools in Ngawen District. The data analysis techniques employed were descriptive statistics and simple linear regression. The findings indicate that the management of digital facilities and infrastructure falls within the good category, with an achievement percentage of 78.6%. The planning aspect obtained the highest score compared to procurement and maintenance. Digital-based learning also demonstrated a high level of effectiveness, particularly in the indicators of material accessibility and student engagement. The results of the regression analysis indicate that facilities and infrastructure management has a significant effect on the effectiveness of digital-based learning, with a coefficient of determination of 64.2%. This study confirms that the success of digital learning is determined not only by the availability of technology, but also by the quality of systematic and sustainable management of educational facilities.